2010
DOI: 10.1176/ps.2010.61.7.690
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences and Similarities in Outpatient Treatment for Depression in the Netherlands

Abstract: The data provided insufficient support for the idea that treatment characteristics are generally less favorable for clients from ethnic minority groups. This finding may be related to the promotion of culturally sensitive approaches to care in mainstream mental health services but may also indicate that the role of traditional barriers, like stigma and taboo, is smaller than is usually suggested. However, the influence of language proficiency, which is notably better among Surinamese and Dutch Antillean compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 53 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…In the Netherlands, like in other European countries, there is a growing number of patients with different ethnic backgrounds which offers an opportunity for cross-cultural comparison. A recent study indicated that stigma and taboo are similar for patients with a depressive or anxiety disorder from Turkey, Morocco, or Surinam [34]. This may be related to the fact that there has been a considerable history of adapting mental health services to suit patients from different cultures.…”
Section: The Netherlandsmentioning
confidence: 99%
“…In the Netherlands, like in other European countries, there is a growing number of patients with different ethnic backgrounds which offers an opportunity for cross-cultural comparison. A recent study indicated that stigma and taboo are similar for patients with a depressive or anxiety disorder from Turkey, Morocco, or Surinam [34]. This may be related to the fact that there has been a considerable history of adapting mental health services to suit patients from different cultures.…”
Section: The Netherlandsmentioning
confidence: 99%
“…(Fassaert et al, 2010, Murray et al, 2010, Ou et al, 2010, Ponce et al, 2006, Poureslami et al, 2010, Puthussery et al, 2010, Sokal, 2010, Timmins, 2002) Research suggests that language barriers adversely affect patients in their access to health services (Jacobs et al, 2006, Pippins et al, 2007, Robert Wood Johnson Foundation, 2001); comprehension and adherence(Cheng et al, 2007, Jacobs et al, 2006); quality of care (Cohen et al, 2005, Diamond et al, 2009, Jacobs et al, 2003, Jacobs et al, 2006); and patient and provider satisfaction. (Arthur et al, 2014, Baker et al, 1996, Jacobs et al, 2006)…”
Section: Introductionmentioning
confidence: 99%
“…This was the case in the Netherlands [ 17 , 37 – 48 ], where the highest prevalence of depressive disorders was observed for Turkish-Dutch, followed by Moroccan-Dutch, while the lowest rates were observed in the native-Dutch group. These figures represented the estimates of mostly first-generation, low educated, Turkish and Moroccan individuals.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, evidence-based therapies for depression, such as pharmacotherapy, Cognitive Behavioral Therapy, and Interpersonal Psychotherapy have barely been investigated in Turkish and Moroccan immigrant groups [ 13 ], with the little existing evidence suggesting low effectiveness in treating depression in Turkish migrant populations [ 14 – 16 ]. Moreover, Turkish and Moroccan patients in secondary care tend to receive less intense psychological treatment and to drop out more often of treatment than the native-born in the Netherlands, partly related to gender, age, and illness characteristics [ 17 ]. The second aim of the review is to describe the factors that are associated to depressive disorders and symptoms (defined in the present paper as “correlates”) in these groups.…”
Section: Introductionmentioning
confidence: 99%